(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The paper discloses the problem of the semantic roles hierarchy in the Slavic sentence inner structure with the subsequent differentiation of agent, object and instrument. The main types of agent in the inner sentence structure based on the differentiation of the predicate and non-predicate character and the typology of the valent classes have been stated for the first time; the latter has been done through the subsequent generalization of the modern concepts of agent definitions and the main differential agent features and their realization in the definite sentence structures have been defined.